KINERJA PENYULUH PERTANIAN LAPANGAN DAN PRODUKTIVITAS USAHATANI PADI SAWAH (KASUS PETANI PADI DI KECAMATAN KALIREJO KABUPATEN LAMPUNG TENGAH) - Tri Pujiana; Tubagus Hasanuddin; Sumaryo Gitosaputro (Lampung University, 2018)
The objectives of this study were to analyze the performance of agricultural extension agents (PPL), factors related to PPL performance, the relationship between PPL performance and productivity of the rice and the relationship between the productivity and paddy rice income in Kalirejo. This study uses a survey method on rice farming in Kalirejo, Central Lampung. The data was collected in October 2017 by interviewing 53 respondents consist of 8 PPLs and 45 rice farmer who were drawn by purposive sampling method. The data was analyzed by qualitative-descriptive analysis, tabulation and Rank Spearman correlation. The study showed that the performance of PPL in BPP Kalirejo was considered high. The competence, work environment, motivation and leadership PPL are related to the performance of PPL. The performance of PPL was related to the productivity of rice. However the productivity was not related to the income of rice farming. Although, the productivity of the rice was increasing, income of the rice farmer was considered low due to low price of rice. Key words: income, performance, productivity